Targeting protein-protein interactions in drug discovery: Modulators approved or in clinical trials for cancer treatment - Cristina Camps-Fajol; Debora Cavero; Jordi Minguillón; Jordi Surrallés (Pharmacological Research)
Protein-protein interactions (PPIs) form complex cellular networks fundamental to many key biological processes, including signal transduction, cell proliferation and DNA repair. In consequence, their perturbation is often associated with many human diseases. Targeting PPIs offers a promising approach in drug discovery and ongoing advancements in this field hold the potential to provide highly specific therapies for a wide range of complex diseases. Despite the development of PPI modulators is challenging, advances in the genetic, proteomic and computational level have facilitated their discovery and optimization. Focusing on anticancer drugs, in the last years several PPI modulators have entered clinical trials and venetoclax, which targets Bcl-2 family proteins, has been approved for treating different types of leukemia. This review discusses the clinical development status of drugs modulating several PPIs, such as MDM2–4/p53, Hsp90/Hsp90, Hsp90/CDC37, c-Myc/Max, KRAS/SOS1, CCR5/CCL5, CCR2/CCL2 or Smac/XIAP, in cancer drug discovery.